Contrasting morphological responses to a singular flood event in neighbouring rivers and the implications for river management : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Geography at Massey University, Manawatū, New Zealand - Coulston, Ethan James (Massey University, 2023)
Geomorphic response to flood events is spatially and temporally variable and is influenced by many natural and anthropogenic processes. Research in recent times has shown the adverse geomorphic effects of rivers that have been managed by straightening, narrowing, and disconnecting them from their floodplain. This work attempts to evaluate the morphological response of small, rural gravel-bed rivers to discrete flood events and to put this response into the context of decadal-scale channel adjustments and river management practices. The Tauanui and Turanganui Rivers in South Wairarapa, New Zealand, were monitored and analysed to identify sediment dynamics within them and how they respond to discrete flood events and river management practices. This was achieved by analysing existing historic aerial and satellite imagery, cross-sectional survey data, and geomorphic change analyses using Structure from Motion (SFM) photogrammetry datasets collected in this project. Historical aerial imagery revealed that both rivers have significantly changed over time, with the area of active gravels reducing 38% in the Tauanui and 48% in the Turanganui River from the 1940s to 2013. A narrowing and straightening of both rivers and a proliferation of heavily vegetated banks was observed. It is suggested that these changes are linked to river management strategies, which have helped to develop floodplains for agriculture and occupation by people. Following a storm event on the 20th of June 2021, flooding caused significant geomorphic change. Geomorphic change analysis before and after suggested net aggradation of 1,564 m³ in the Tauanui River and 3,430 m³ in the Turanganui River. Although geomorphic change was significant in both study reaches, it contrasted. This contrast has been interpreted as a result of differences in river resilience and geomorphic thresholds. Similar to other studies, it is suggested that river management interventions have reduced resilience and brought both rivers closer to geomorphic thresholds. This has resulted in geomorphic change that is disproportionate to the flood magnitude. River management that homogenises river corridors is also detrimental to habitat diversity and increases the exposure of the surrounding land to flood risk.
The following Figures were removed for copyright reasons: Fig 7 (=Chappell, 2014 Fig 10); 11 (=Cape et al., 1990, Fig 2); 13 (=Bertaud-Gandar et al., 2018 Fig 1); 14 (=Corenblit et al., 2015 Fig 4); 15 (=Sear et al., 1995 Fig 6); 17 (=Fuller et al., 2019a Fig 1); 18 (=Fryirs & Brierley, 2000 Fig 1); 19 (=Harvey 2007, Fig 2); 20 (= Fuller, 2008 Fig 4); 21 (=Fuller et al., 2003 Fig 8); 22 (=Brasington et al., 2000 Figs 2 & 3); 23 (=Charlton et al., 2003 Fig 3); 24 (=Lallias-Tacon et al., 2014 Fig 3); 32 (=Cook, 2017 Fig 7B); 37 (=Larsen et al., 2006 Fig 8A); 91A (=Wyzga, 1993 Fig 3A); 92 & 97 (=Garcia et al., 2021 Figs 2 & 3); 95 Piegay et al., 2005 Fig 5B); 96 (=Williams et al., 2020 Graphical abstract). Figs 25, 26, 27, 34 & 35 and Table 1 are reproduced under a CC BY 4.0 DEED license. Fig 29 is reproduced under a CC BY 3.0 DEED license.
Keywords: 370704 Surface water hydrology; 370901 Geomorphology and earth surface processes